Exploring the clinical value of tumor microenvironment in platinum-resistant ovarian cancer. (December 2021) - Ghoneum, Alia; Almousa, Sameh; Warren, Bailey; Abdulfattah, Ammar Yasser; Shu, Junjun; Abouelfadl, Hebatullah; Gonzalez, Daniela; Livingston, Christopher; Said, Neveen
Abstract: Platinum resistance in epithelial ovarian cancer (OvCa) is rising at an alarming rate, with recurrence of chemo-resistant high grade serous OvCa (HGSC) in roughly 75 % of all patients. Additionally, HGSC has an abysmal five-year survival rate, standing at 39 % and 17 % for FIGO stages III and IV, respectively. Herein we review the crucial cellular interactions between HGSC cells and the cellular and non-cellular components of the unique peritoneal tumor microenvironment (TME). We highlight the role of the extracellular matrix (ECM), ascitic fluid as well as the mesothelial cells, tumor associated macrophages, neutrophils, adipocytes and fibroblasts in platinum-resistance. Moreover, we underscore the importance of other immune-cell players in conferring resistance, including natural killer cells, myeloid-derived suppressive cells (MDSCs) and T-regulatory cells. We show the clinical relevance of the key platinum-resistant markers and their correlation with the major pathways perturbed in OvCa. In parallel, we discuss the effect of immunotherapies in re-sensitizing platinum-resistant patients to platinum-based drugs. Through detailed analysis of platinum-resistance in HGSC, we hope to advance the development of more effective therapy options for this aggressive disease.